2010
DOI: 10.2131/jts.35.817
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic potentials of Amberlite XAD-2-resin extracts obtained from river and drinking waters in the Northwest district of Chiba, Japan

Abstract: -Amberlite XAD-2 resin extracts of river and drinking water sampled from the Northwest district of Chiba Prefecture in each month during the period from January to December 2008 were investigated to characterize and determine their mutagenic potentials and polycyclic aromatic hydrocarbon (PAH) levels. The extracts from the river water were shown to be mutagenic in Salmonella typhimurium TA98 (a flameshift mutagen) without S9 mix, with higher mutagenic responses in summer and early fall seasons. While the drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
2
0
2
Order By: Relevance
“…TA98 Salmonella strain was by far the most sensitive strain, 99% of the positive samples showed mutagenic activity with that strain, regardless the presence of metabolic activation, or positive results also detected with other strains. The same kind of results were observed by Kanno et al (2010), andLv et al (2015), and pointed out in the review by Ohe et al (2004), as well. In our study, positive results were detected with TA98 and not detected with TA100 (or YG1042, see below) in 234 samples, of which 83 were positive with and without metabolic activation (24% of all positive samples), 113 exclusively without S9, and 38 exclusively with S9 (32% and 11% of all mutagenic samples, respectively).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…TA98 Salmonella strain was by far the most sensitive strain, 99% of the positive samples showed mutagenic activity with that strain, regardless the presence of metabolic activation, or positive results also detected with other strains. The same kind of results were observed by Kanno et al (2010), andLv et al (2015), and pointed out in the review by Ohe et al (2004), as well. In our study, positive results were detected with TA98 and not detected with TA100 (or YG1042, see below) in 234 samples, of which 83 were positive with and without metabolic activation (24% of all positive samples), 113 exclusively without S9, and 38 exclusively with S9 (32% and 11% of all mutagenic samples, respectively).…”
Section: Resultssupporting
confidence: 84%
“…We looked for seasonal effects and found that from the total of positive samples (348), we observed similar percentages in spring (24%), fall (24%), and in summer (21%), and a lower value in winter (13%). Kanno et al (2010) and Watanabe et al (2002) observed that in river waters from Japan, mutagenicity was higher in summer and fall, and Umbuzeiro et al (2001) showed higher incidence of mutagenicity in summer, as well.…”
Section: Resultsmentioning
confidence: 96%
“…Many traditional biological approaches have been used to evaluate health risk of drinking water, such as Ames test 29 and comet assay. 30 However, these studies focused on the effects of extracts with much higher concentrations of pollutants than natural water.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Původní postup pročištění methanolem a následný oplach demineralizovanou vodou byl na základě dat získaných rešerší upraven. Reziny byly pročišťovány a kondiciovány v soxhletových extraktorech po dobu 8 hodin methanolem a následně 8 hodin acetonem [22]. Jde totiž o rozpouštědla, která jsou v dalších krocích testování používána i při samotné extrakci sorbovaných látek a jsou také doporučována výrobci XAD rezinů (např.…”
Section: úVodunclassified
“…Takto vzniklé methanolové a acetonové extrakty byly nejprve zahuštěny do objemu 5 ml na vakuové rotační odparce Heidolph (při teplotě vodní lázně 50 °C, při tlaku 300 mbar pro methanolový extrakt a 550 mbar pro acetonový extrakt) [22][23][24][25]. Do konečného objemu 100 µl byly extrakty dofoukány dusíkem.…”
Section: Metodikaunclassified